Деякі аспекти озеленення техногенних територій - Yusypiva, T.I.; Gritzay, Z.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The decrease of the young woody plant samples quantity, their growth inhibition under the influence of toxic SO2 and NO2 gases on the plant species was investigated. It was offered to use the plants of the virgin group of the tolerant woody species as material for green planting in technogenic territories.